Description of two new Obriini Mulsant, 1839 (Coleoptera: Cerambycidae) from the Tankwa Karoo biome in South Africa and Namibia - Maquart, Pierre-Olivier; Richard, Denis; Vitali, Francesco (Zootaxa, 2018)
Two new species of Capezoum: C. tankwakarooensis sp. nov. and C. museiconfluentiarum sp. nov. are described from the Succulent Karoo ecosystem in South Africa and Namibia.